Thermal breakdown in high voltage direct current cable insulations due to space charges. Issue 5 (3rd September 2018) - Jörgens, Christoph; Clemens, Markus
Abstract : Purpose: In high voltage direct current (HVDC), power cables heat is generated inside the conductor and the insulation during operation. A higher amount of the generated heat in comparison to the dissipated one, results in a possible thermal breakdown. The accumulation of space charges inside the insulation results in an electric field that contributes to the geometric electric field, which comes from the applied voltage. The total electric field decreases in the vicinity of the conductor, while it increases near the sheath, causing a possible change of the breakdown voltage. Design/methodology/approach: Here, the thermal breakdown is studied, also incorporating the presence of space charges. For a developed electro-thermal HVDC cable model, at different temperatures, the breakdown voltage is computed through numerical simulations. Findings: The simulation results show a dependence of the breakdown voltage on the temperature at the location of the sheath. The results also show only limited influence of the space charges on the breakdown voltage. Research limitations/implications: The study is restricted to one-dimensional problems, using radial symmetry of the cable, and does not include any aging or long-term effect of space charges. Such aging effect can locally increase the electric field, resulting in a reduced breakdown voltage. Originality/value: A comparison of the breakdown voltage with and without space charges is novel. The chosen approach allows for the first time to assess the influence of space charges and field inversion on the thermal breakdown.